2015
DOI: 10.1097/wad.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Mid-life Cardiovascular Risk Impacts Memory Function

Abstract: Introduction This study incorporates unique error response analyses with traditional measures of memory to examine the association between mid-life cardiovascular risk factors (CVRF) and later-life memory function. Methods The Framingham Stroke Risk Profile (FSRP), a composite score of cardiovascular risk, was assessed in 1755 Framingham Offspring participants (54% women, mean age=54±9 years) from 1991-1995. Memory tests including Logical Memory (LM) and Visual Reproductions (VR) were administered from 2005-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
2
18
1
Order By: Relevance
“…The association between AD and high vascular scores from the Framingham study has already been studied. Jefferson et al investigated the association between FCRP and deterioration of cognitive assessment in cognitively healthy subjects and patients with MCI [35], while the Framingham Offspring Study showed a correlation between FCRP and cognitive impairment in APOE ε4 carriers with several cardiovascular risk factors [36,37]. Another relevant aspect is that, as opposed to genetic and liquoral biomarkers, vascular and metabolic alterations are modifiable factors.…”
Section: Discussionmentioning
confidence: 99%
“…The association between AD and high vascular scores from the Framingham study has already been studied. Jefferson et al investigated the association between FCRP and deterioration of cognitive assessment in cognitively healthy subjects and patients with MCI [35], while the Framingham Offspring Study showed a correlation between FCRP and cognitive impairment in APOE ε4 carriers with several cardiovascular risk factors [36,37]. Another relevant aspect is that, as opposed to genetic and liquoral biomarkers, vascular and metabolic alterations are modifiable factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cigarette smoking, a major cause of COPD, is associated with decreased cognitive function and increased cognitive decline ( 4 , 15 17 ); the 2011 Behavioral Risk Factor Surveillance System (BRFSS) showed that almost 40% of adults with COPD that year were smokers ( 18 ). Furthermore, COPD frequently co-occurs with other chronic conditions ( 19 21 ), many of which also can involve cognitive impairment, such as heart and vascular diseases ( 22 , 23 ), diabetes ( 24 ), and stroke ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…83 Chronically elevated blood pressure promotes cerebrovascular remodeling, leading to a reduction in the lumen diameter by an increase in the wall-to-lumen ratio. 84 Additional consequences of prolonged systemic blood pressure include altered morphology of small cerebral arterioles that supply vulnerable brain regions necessary for cognitive function.…”
Section: Hypertensionmentioning
confidence: 99%